PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS XI FASE F MOVING CLASS SOSIOLOGI R5 SMAN 1 SITIUNG - Salsabila, Annisa; Sarbaitinil, Sarbaitinil; Wahyuni, Yanti Sri (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on improving students' problem-solving abilities in sociology learning, particularly among Grade XI Phase F students at SMA Negeri 1 Sitiung who initially demonstrated passive learning behavior and limited ability in identifying and solving problems. The research employed a quantitative approach with a quasi-experimental design, involving two purposively selected classes: one as the experimental group (36 students) that received instruction using the PBL model, and the other as the control group (36 students) that received conventional instruction. Data collection instruments consisted of problem-solving ability tests and a PBL response questionnaire, which was administered exclusively to the experimental group. The data were analyzed using descriptive statistics, normality and homogeneity tests, and an independent t-test. The results revealed a significant difference in posttest scores between the two groups, with the experimental group achieving a higher mean score of 84.81 compared to 69.56 in the control group. The t-test also showed that the calculated t-value (7.79) was greater than the critical t-table value (1.99), indicating a statistically significant effect of the PBL model on students’ problem-solving skills. The novelty of this research lies in its application of the PBL model within sociology instruction—specifically on the topic of social conflict—in the context of Mooving Class Phase F